Global Applications of the Japanese ‟Lesson Study” Teacher Education and Training Model - Duez, Erin (International Dialogues on Education Journal, 2018)
“Lesson study” has been used for over a century in Japan (Makinae, 2010). However, only recently, in 1999 with the release of The Teaching Gap by Stigler and Hiebert, did the practice begin to spread globally (Fujii, 2013; Ebaeguin & Stephens, 2013). The Teaching Gap is a summary of the Third International Math and Science (TIMSS) video study and included an entire chapter titled “Beyond Reform: Japan’s approach to the improvement of classroom teaching.” This chapter stated that the way the United States was reforming education was not systematic and offered lesson study in eight steps as a way to improve teaching and learning (Stigler & Hiebert, 1999). From 2000-2006 the lesson study process spread across the globe to nations including Indonesia, United States, England, Philippines, Australia, Sweden, and several African Nations (Groves & Doig, 2014). This paper will describe Japan’s lesson study process and the successes and failures of global application.